Inhibitory and excitatory responses in the dorso-medial prefrontal cortex during threat processing - Chirumamilla, Venkata C.; Gonzalez-Escamilla, Gabriel; Meyer, Benjamin; Anwar, Abdul Rauf; Ding, Hao; Radetz, Angela; Bonertz, Tamara; Groppa, Sergiu; Muthuraman, Muthuraman (Frontiers in Neuroscience, 2023)
Objective: To evaluate cortical excitability during instructed threat processing.. Methods: Single and paired transcranial magnetic stimulation (TMS) pulses were applied to the right dorsomedial prefrontal cortex (dmPFC) during high-density electroencephalography (EEG) recording in young healthy participants (n=17) performing an instructed threat paradigm in which one of two conditioned stimuli (CS+ but not CS-) was paired with an electric shock (unconditioned stimulus [US]). We assessed TMS-induced EEG responses with spectral power (both at electrode and source level) and information flow (effective connectivity) using Time-resolved Partial Directed Coherence (TPDC). Support vector regression (SVR) was used to predict behavioral fear ratings for CS+ based on TMS impact on excitability. Results: During intracortical facilitation (ICF), frontal lobe theta power was enhanced for CS+ compared to single pulse TMS for the time window 0-0.5 s after TMS pulse onset (t(16) = 3.9,p < 0.05). At source level, ICF led to an increase and short intracortical inhibition (SICI) to a decrease of theta power in the bilateral dmPFC, relative to single pulse TMS during 0-0.5 s. Compared to single pulse TMS, ICF increased information flows, whereas SICI reduced the information flows in theta band between dmPFC, amygdala, and hippocampus (all at p < 0.05). The magnitude of information flows between dmPFC to amygdala and dmPFC to hippocampus during ICF (0-0.5 s), predicted individual behavioral fear ratings (CS+; coefficient above 0.75). Conclusion: Distinct excitatory and inhibitory mechanisms take place in the dmPFC. These findings may facilitate future research attempting to investigate inhibitory/facilitatory mechanisms alterations in psychiatric disorders and their behavioral correlates.